Efecto potenciador del caldo sulfocálcico en la toxicidad de extractos de barbasco clavija sp - neem para el control de colaspis submetallica y sibine sp en banano orgánico - Intriago, Mayra (2006)
In the Parish Caña Quemada, and in the Celia María Farm, during the period June to October of the 2005, formulated insecticides were elaborated with extracts of barbasco Clavija sp. and the potential effect of the sulphocalcic broth was studied in the toxicity of the insecticides compound among other components for extract of pepper, verbena, neem and vegetable piretro. The objectives were: 1. to determine the potential or antagonistic effect of polisulphur and extracts of pepper, verbena in the toxicity of the barbasco and associated with commercial neem; 2. to study the toxicity of five formulations of barbasco extracts enriched with sulphocalcic against adults of Colaspis and larva of Sibine sp. and 3. to elaborate the toxicity curve by means of bioassay up to 90 days after the elaboration of the products. here were prepared watery extracts of barbasco at 30% and ethanolics of pepper at 20%. Sulphocalcic broth, by means of the mixture of elementary sulfur and oxide of calcium or alive lime in water subjecting to boil during one hour until it took a reddish color. Other used ingredients were: commercial neem, verbena extracts (Verbena litoralis KBK, eatable oil and Triton X 45), and starting from these ingredients six formulations were elaborated and designated as treatments for the phototoxicity studies against Colaspis and Sibine. In several bioassays with adults of Colaspis submetalica J. and larva of 4th at 6th stage of Sibine sp it was determined the toxicity of the obtained products, by means of contact tests and ingestion in the case of the second species, adjusting the assay from the coleopteron to a design in blocks at random with five application dates in the month of July of the 2005 in which was registered the populational pick. With the second species the design was Completely randomized. The toxicity tendency curve of the treatments was elaborated with the results obtained in three bioassays carried out with adults of Metamasius hemipterus. The results evidence that the increment of broth sulphocalcic among 10 to 15% in the insecticide formulations to control Colaspis submetalica, did not potencies the toxicity, when being determined a light decrement of the corrected mortality in the first three formulations elaborated with this ingredient. The preparations have the inconvenience of being phytotoxic. The mortality of adults of the coleopteron at the four hours overcame 80%. The toxicity of the preparations, goes falling in the time until the 90 days after its elaboration and that takes place a separation of the components of the initial emulsion. Of the prepared formulations with Neem to control appearance of false montura Sibine sp. the F1, Barnasco-Sulfocal-oil Neem, was the most efficient.